Knee arthrodesis with ring fixator for lower limb salvage after necrotizing fasciitis involving extensor apparatus - Sousa, Paula Alves; Pimentel, Miguel; Quesado, Miguel; Dores, João Das (International Journal of Research in Orthopaedics, 2025)
Necrotizing fasciitis (NF) is a rare but severe infection with high morbidity and mortality, requiring urgent and aggressive intervention. This case describes a 64-year-old male who presented with septic arthritis of the knee complicated by NF and Streptococcal toxic shock syndrome. Despite early surgical debridement and empiric antibiotic therapy, the infection progressed, resulting in extensive necrosis of the knee extensor apparatus and exposure of the knee joint. Knee arthrodesis with a circular external fixator was performed, allowing for joint stabilization, soft tissue closure with skin grafts, and comprehensive functional rehabilitation. Six months post-discharge, the patient achieved pain-free, independent ambulation, avoiding amputation. This case underscores the feasibility of knee arthrodesis with a circular external fixator as a viable option for limb salvage in severe NF cases.